2021
DOI: 10.1007/s11747-020-00762-y
|View full text |Cite
|
Sign up to set email alerts
|

Understanding anthropomorphism in service provision: a meta-analysis of physical robots, chatbots, and other AI

Abstract: An increasing number of firms introduce service robots, such as physical robots and virtual chatbots, to provide services to customers. While some firms use robots that resemble human beings by looking and acting humanlike to increase customers’ use intention of this technology, others employ machinelike robots to avoid uncanny valley effects, assuming that very humanlike robots may induce feelings of eeriness. There is no consensus in the service literature regarding whether customers’ anthropomorphism of rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
428
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 528 publications
(445 citation statements)
references
References 124 publications
15
428
0
2
Order By: Relevance
“…While marketing has found anthropomorphism to increase product and brand liking (Aggarwal and McGill, 2012), it is unclear whether anthropomorphism in a frontline service triad including service robots enhances customers' repatronage. Contemporary service research acknowledges the importance of the human tendency to anthropomorphize robots (Mende et al, 2019;Van Doorn et al, 2017), but the question remains whether customers' anthropomorphism of robots facilitates or constrains use intention (Blut et al, 2021).…”
Section: Anthropomorphismmentioning
confidence: 99%
See 1 more Smart Citation
“…While marketing has found anthropomorphism to increase product and brand liking (Aggarwal and McGill, 2012), it is unclear whether anthropomorphism in a frontline service triad including service robots enhances customers' repatronage. Contemporary service research acknowledges the importance of the human tendency to anthropomorphize robots (Mende et al, 2019;Van Doorn et al, 2017), but the question remains whether customers' anthropomorphism of robots facilitates or constrains use intention (Blut et al, 2021).…”
Section: Anthropomorphismmentioning
confidence: 99%
“…Utilitarian value suggests that JOSM customers will have more confidence in the accuracy and consistency of the service provided, whereas service robot's hedonic value relates to fun and entertainment (Arnold and Reynolds, 2003;Lu et al, 2019;Ryan and Deci, 2001). Service providers implement anthropomorphic service robots to create value and encourage customer loyalty (Blut et al, 2021;Zemke et al, 2020). Therefore, for our context of hospitality services, we expect that being perceived as a human as the first degree of social response (anthropomorphism) translates into the provision of the core service such as serving food and drink rather than into entertaining guests.…”
Section: Hypotheses Development and Conceptual Modelmentioning
confidence: 99%
“…We had highlighted this type of innovation in the call for papers, as it is increasingly prevalent, but is still understudied. We are excited to see the special issue open with a lead article that provides a comprehensive summary of research in this area to date (Blut et al, 2021). The authors present a metaanalysis that synthesizes data from 11,053 individuals interacting with AI-powered service robots reported in 108 independent samples.…”
Section: New Types Of Innovation In the Digital Economymentioning
confidence: 99%
“…preference (Wang et al, 2020), and greater intention to use a service robot (for a recent review, see Blut et al, 2021). For example, Delbaere and colleagues (Delbaere et al, 2011) reported that the more positive affect derived from advertising anthropomorphism would increase consumers' preferences for the advertised brand.…”
Section: Food Shape and Consumer Preferences: Affect As Informationmentioning
confidence: 99%